The gender-specific expression of neuropeptide Y and neuropeptide Y receptors in human atrial tissue during cardiopulmonary bypass surgery - Meng, Fei; Han, Jie; Wang, Jiangang; Zhang, Haibo; Xu, Chunlei; Meng, Xu (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Background: Cardiac sympathetic nervous system is usually activated in cardiopulmonary bypass (CPB) surgery, accompanied by excessive release of norepinephrine (NE). Neuropeptide Y (NPY) has been shown to regulate NE release in the terminal of sympathetic fiber, which is a target for regulating heart function. The expression of NPY and NPY receptor (NPYR) genes in the human atrial tissues during CPB in cardiac surgery was investigated in the present study. Methods: A few discarded atrial tissues before and after CPB were collected in 22 patients with rheumatic cardiac valve diseases. The transcriptional levels of NPY and NPYRs were monitored by real-time quantitative polymerase chain reaction (RT-qPCR) method. Moreover, the correlation between the mRNA levels of NPY/NPYRs and the clinical data were investigated in detail. Results: The mRNA levels of NPY Y1 and NPY Y5 genes were statistically attenuated in male patients after CPB. Conversely, the expression of NPY, NPY Y1 and NPY Y5 genes were enhanced in female patients. Correlation analysis suggested that there was a significant negative correlation between cardiac ejection fraction (EF) after CPB with the atrial transcriptional level of NPY in male patients. Conclusions: These results suggested that the expression of NPY/NPYRs in human atrial tissue during CPB was gender specific and activated NPY signaling was only identified in female patients. The elevated expression level of NPY in male patients was correlated with lower cardiac EF after CPB.